The role of IL-35 and IL-37 in breast cancer – potential therapeutic targets for precision medicine - Ma, Yuntao; Su, He; Wang, Xuyun; Niu, Xiangdong; Che, Yang; Hambly, Brett D.; Bao, Shisan; Wang, Xiaopeng (Frontiers in Oncology, 2022)
Breast cancer is still a major concern due to its relatively poor prognosis in women, although there are many approaches being developed for the management of breast cancer. Extensive studies demonstrate that the development of breast cancer is determined by pro versus anti tumorigenesis factors, which are closely related to host immunity. IL-35 and IL-37, anti-inflammatory cytokines, play an important role in the maintenance of immune homeostasis. The current review focuses on the correlation between clinical presentations and the expression of IL-35 and IL-37, as well as the potential underlying mechanism during the development of breast cancer in vitro and in vivo. IL-35 is inversely correlated the differentiation and prognosis in breast cancer patients; whereas IL-37 shows dual roles during the development of breast cancer, and may be breast cancer stage dependent. Such information might be useful for both basic scientists and medical practitioners in the management of breast cancer patients.